Aeroacoustic Effect of Savonius Rotor Segmentation - SACHAR, Shivangi; DOERFFER, Piotr; FLASZYŃSKI, Paweł; KOTUS, Józef; DOERFFER, Krzysztof; GRZELAK, Joanna; PIOTROWICZ, Michał (Archives of Acoustics, 2025)
Switching to renewable energy has been accelerated in recent decades due to the depleting fossil fuel reserves and the need to mitigate environmental and climate degradation. Wind power, especially in urban areas, has seen a significant growth. A critical consideration in the urban wind turbine installation is the noise impact on residents. This study investigates the noise generated by wind turbines under different operational conditions, comparing single-segment and five-segment rotor designs. Various acoustic analyses were conducted, including broadband analysis with weighting curves Z, A, C, and G, a narrowband analysis using 1/12 octave bands, and broadband calculations of sound quality indicators such as sharpness, roughness, and fluctuation strength (FS). The FS was also examined in the Bark scale frequency domain. The study linked the acoustic analysis with the rotor efficiency related to power production. The findings indicate that five-segment rotors generate less acoustic energy due to phase shifts, enhancing dissipation rates, and acoustic energy decreases with the increasing load, peaking when rotors are free at high revolutions per minute (RPM). While single-segment rotors show higher efficiency, they produce more noise. In contrast, five-segment rotors offer a better sound quality, making them preferable despite a lower efficiency. This research provides essential insights into designing urban wind turbines that balance efficiency and noise, crucial for sustainable energy solutions.